Competitive‐Binding Activated Supramolecular Nanovalves Based on β‐Cyclodextrin Complexes. Issue 19 (4th July 2017) - Liu, Zongjun; Shi, Junhui; Han, Renlu; Wang, Hao; Wang, You; Gan, Yang
Abstract: Competitive binding activated nanovalves (CBAN) with on‐demand activation capability are fabricated through switching from host‐guest complexation to decomplexation upon the introduction of competitive guest (C‐guest) molecules. Guest molecules of pyrene or naphthalene are used to associate with β ‐cyclodextrin ( β ‐CD) host to form supramolecular complexes. These supramolecular conjugations were assembled on the surface of mesoporous silica nanoparticles (MSNs), which played a role of "nanovalve" for blocking the nanopores. For the activation of nanovalves, C‐guest of 1‐adamantanamine hydrochloride (Ad), was added to dissociate formerly assembled complex by competitive binding with host β ‐CD. In controlled release study, the fabricated CBAN was stable at "Off" state for preventing cargo release, and able to release the cargo efficiently at "On" state. Moreover, the competitive binding process was also investigated by using fluorescein isothiocyanate modified β ‐CD. It was found that the shift of host‐guest complexation equilibrium by C‐guest activates the CBAN. These results would shed lights on the development of novel supramolecular nanovalves. Abstract : Competitive binding activated nanovalves based on β ‐cyclodextrin ( β ‐CD) complexes were synthesized for controlled release application. β ‐CDs were used to associate with guest molecules (pyrene or naphthalene) on mesoporous silica nanoparticles to form supramolecular complexes for blocking the nanopores. To activate the nanovalves, competitive guest was added to dissociate assembled complex via competitive binding with β ‐CD. The competitive binding mechanism was investigated, and it was found that the shift of host‐guest complexation equilibrium by competitive guest activated the nanovalve.